SOME ISSUES OF DETERMINING THE MAXIMUM SHEAR RESISTANCE OF THE LAYERED SOILS (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The article discusses some issues of determining the shear resistance of the layered soils. The problem of determining the maximum shear resistances when the shear stresses are perpendicular to the layering is considered. It has been theoretically shown that when shear stresses act perpendicular to layering, tensile strength is achieved at lower values of shear stress than the total shear resistance. When determining the stability of a slope composed of layered soils, it is proposed to take the maximum shear resistance values of laboratory tests.
Keywords: theoretically; clays; shear resistance; layered soils